2006
DOI: 10.1016/j.contraception.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen-only contraception and bone mineral density: a systematic review

Abstract: Questions have been raised about the effects of progestogen-only contraceptive use on bone health, particularly among young women who have not yet reached peak bone mass and perimenopausal women who may be starting to lose bone mass. We conducted a systematic review that evaluated the association between progestogen-only contraceptive use and fracture risk or bone mineral density (BMD). We identified 39 articles from MEDLINE and EMBASE, published through July 2005. One study reported that depot medroxyprogeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 52 publications
4
60
0
8
Order By: Relevance
“…However, the associations between progestogen implants and BMD are again conflicting [17], studies of other types of progestogen-only contraceptives were few and restricted to lactating women [18]. Our data suggested a weak positive association between progestogenonly contraceptive use (all types combined) and bone mass which is consistent with a recent review that use of progestogen-only contraceptives other than DMPA did not affect BMD [7]. However, our sample of progestogen-only users was too small to draw firm conclusions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the associations between progestogen implants and BMD are again conflicting [17], studies of other types of progestogen-only contraceptives were few and restricted to lactating women [18]. Our data suggested a weak positive association between progestogenonly contraceptive use (all types combined) and bone mass which is consistent with a recent review that use of progestogen-only contraceptives other than DMPA did not affect BMD [7]. However, our sample of progestogen-only users was too small to draw firm conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, several studies have examined the associations in young women and also presented inconclusive results [2][3][4][5], with negative associations in samples recruited from a university or from fit, heavily exercising female military cadets [2,3], and a beneficial effect in female athletes over 2 years follow-up [4]. Progesterone only contraceptives, such as depot medroxyprogesterone acetate (DMPA), have been associated with lower BMD in young women [6] but studies of other types of progestogen-only contraceptives and BMD are limited [7]. The associations between OC use and risk of fractures are mixed though DMPA users were more likely to experience stress fractures than non-users [7].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, numerous studies have shown that women who use depot-medroxyprogesterone (DMPA) lose small amounts of bone mineral density [19]; much, if not all, of the bone mineral density is regained upon discontinuation of DMPA [20]. These findings have led to concern about the potential for fracture among DMPA users.…”
Section: Putting Risk Into Perspectivementioning
confidence: 98%
“…Badania nie wykazały negatywnego wpływu niskodawkowej antykoncepcji zawierającej tylko progestageny na gęstość tkanki kostnej [45].…”
Section: Gęstość Mineralna Kościunclassified